2017
DOI: 10.1007/s00404-017-4643-y
|View full text |Cite
|
Sign up to set email alerts
|

Membrane sweeping added to formal induction method to increase the spontaneous vaginal delivery: a meta-analysis

Abstract: MS added to formal induction significantly increased vaginal delivery rates, especially in nulliparas compared with formal induction alone. Notably, there are no obvious side effects of MS. Meanwhile, more RCTs studies are needed to investigate the side effects of MS on instrumental delivery, postpartum hemorrhage, and cervical laceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In a 2018 meta-analysis of 6 RCTs (N = 1133 participants), Liu and colleagues compared 2 groups of participants: cervical balloon (30-60 mL fill) followed by standard dose oxytocin for IOL or cervical balloon with simultaneous initiation of oxytocin. 27 They found that multiparous participants in both groups were equally likely to give birth within 24 hours. However, nulliparous participants using a cervical balloon with simultaneous synthetic oxytocin experienced a 32% increased likelihood of birth within 24 hours (RR, 1.32; 95% CI, 1.12-1.55) compared with nulliparous participants using the cervical balloon with the later addition of synthetic oxytocin.…”
Section: Combination Methods For Cervical Ripeningmentioning
confidence: 98%
See 4 more Smart Citations
“…In a 2018 meta-analysis of 6 RCTs (N = 1133 participants), Liu and colleagues compared 2 groups of participants: cervical balloon (30-60 mL fill) followed by standard dose oxytocin for IOL or cervical balloon with simultaneous initiation of oxytocin. 27 They found that multiparous participants in both groups were equally likely to give birth within 24 hours. However, nulliparous participants using a cervical balloon with simultaneous synthetic oxytocin experienced a 32% increased likelihood of birth within 24 hours (RR, 1.32; 95% CI, 1.12-1.55) compared with nulliparous participants using the cervical balloon with the later addition of synthetic oxytocin.…”
Section: Combination Methods For Cervical Ripeningmentioning
confidence: 98%
“…However, parity influenced outcomes; for nulliparous participants there was a 32% increase in spontaneous vaginal birth within 48 hours (RR, 1.32; 95% CI, 1.18‐1.48) with first‐examination membrane sweeping, whereas there were no differences in rates of spontaneous vaginal birth in 48 hours in multiparous participants. No adverse maternal or neonatal outcomes were noted with membrane sweeping 27 . Thus, there appear to be advantages for pregnant people of having their membranes swept, both in terms of avoiding labor induction and for increasing the likelihood of spontaneous vaginal birth in the first 2 days of IOL when used to initiate induction in nulliparous people.…”
Section: Cervical Ripeningmentioning
confidence: 93%
See 3 more Smart Citations